Corrosion characteristics of cold gas spray coatings of reinforced aluminum deposited onto carbon steel - Silva, F.S.da [UNESP] (2017)
The morphology, chemical, mechanical and corrosion characterization of starting materials, and Al and Al-Al2O3/Al coatings obtained by Cold Gas Spray and applied on common steel substrate were performed. An Al coating on a ground or grit blasted substrate, and Al-Al2O3/Al coating on ground mild carbon steel have been compared. The electrochemical results showed that the coatings protect the substrate for immersion times >2000 h due to the dense structure obtained by Al and Al-Al2O3. The electrolyte reaches the substrate only after 2000 h of immersion without wetting completely the coating/substrate interface. Coatings have resisted 3000 h of salt fog test.